Levantamento da fauna ixodológica em Chelonoidis denticulatus no ambiente do Parque Natural Municipal Florestal de Sinop (MT), e detecção da circulação de Rickettsia spp. - Pinho, Vanderson de Souza (2022)
The Sinop Municipal Natural Forest Park (PNMF) was idealized with the objective of preserving fragments of native forest and providing leisure to the Sinopense community, for being in the urban area of the city. The Brazilian Spotted Fever (FMB) is a zoonotic infectious disease, reemerging in some regions of Brazil, causing clinical symptoms ranging from acute febrile illness to the involvement of vital organs; being caused by the Rickettsia rickettsia bacteria. In Brazil, it is transmitted main ly by the biteo fixo did ticks of the genus Amblyomma. In the northern region of Mato Grosso, studie son the ixodological fauna and agent transmission are still incipient. The objective of this study was to survey the ixodological fauna in Chelonoidis denticulatus and analyze its role as a reservoir of Rickettsia spp. in the Parque Natural Municipal Florestal (PNMF) of Sinop, which is a fragment of the city's native forest and provides leisure to the community. Ticks were collected every o three-week for 12 months, from March 2020 to March 2021, in the central area of the PNMF, using visual observation techniques of the vegetation, manual scavenging in Chelonoidis denticulatus and dragging technique with white flannel in open field areas and trails. Collected specimens were stored in flasks with absolute alcohol and identified using specific identification keys for ixodids. A total of 1,191 ticks were collected, including 49 larvae of Amblyomma sp.; 4 females and 2 nymphs of Amblyomma rotundatum; 1 male and 1 female of Amblyomma romitti; 862 males, 167 females and 105 nymphs of Amblyomma humerale. Of these, 99.07% (1,180) ticks pecimens were collected on Chelonoidis denticulatus 0.75% (9) were collected on there searchers' clothing, and 0.16% (2) were collected by trawling with a flannel in the environment. Afterwards, DNA samples from 160 ticks of the genus Amblyomma were submitted to PCR for detection of rickettsia DNA. All samples analyzed were negative for Rickettsia spp.